PROMOSI MEDIA SOSIAL DI OBJEK WISATA DEPATI VII COFFEE KOTA SUNGAI PENUH PROVINSI JAMBI - Nurza, Della Normareta; Martina, Elti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This research is motivated by the lack of optimal use of social media by most tourist attractions in Sungai Penuh City. Depati VII Coffee is the most active and consistent tourist attraction that utilizes social media, especially Instagram, compared to other natural attractions in the region. This study aims to find out how Depati VII Coffee's social media promotion is implemented and how visitors respond to this strategy. The research method used is a quantitative approach with simple random sampling techniques, using a Likert scale closed questionnaire to visitors. The data were analyzed descriptively with the help of the IBM SPSS Statistics 27 application. The results of the study show that the promotion strategy through Instagram has been effective. The context variable obtained a mean value of 4.15 which indicates that the promotional message is considered interesting and relevant. The communication variable recorded the highest value of 4.17, indicating responsive and informative communication. The collaboration variable received a value of 3.86, describing a collaboration that is quite good but can still be improved, while the connection with a value of 3.92 shows the loyalty and attachment of followers to the Depati VII Coffee account. Keywords: Social media Promotion, Instagram, 4C Social media Marketing, Depati VII Coffee, Tourism